Implementation of Neuroscience-Based Multiple Intelligences Theory: To Improve the Intelligence of Students in Ma'had - Jailani, Mohammad; Yoyo, Yoyo; Suyadi, Suyadi; Huda, Miftachul; Ahmadi, Ahmadi (Universitas Islam Negeri Raden Intan Lampung, 2022)
The development of the flow of Arabic knowledge at the pesantren level (Madrasah Aliyah, Madrasah Diniyah, and Madrasah Ta'wiliyah). Demanding increased Arabic learning to santri. However, this is inversely proportional to the fact that students are declining in developing Arabic mufrodat and linguistics material. This study aims to analyze the Arabic language learning model based on multiple intelligences from a neuroscience perspective. The setting of this research is located in the Himmatul ‘Amilin Islamic Boarding School in Yogyakarta. The subjects of this research consisted of the leaders of Islamic boarding schools, musyrif, and ustadz. Subject selection was carried out using the purposive sampling technique to obtain objective and valid data. The approach in this research is to use a case study-based qualitative method. Researchers in collecting data using observation methods, direct interviews, and documentation. The data analysis technique was followed by Milies and Huberman, namely by displaying data, reducing data, and verifying data. The results of this study explain that learning Arabic based on multiple intelligences increases the intelligence of students in learning Arabic mufradat and linguistics (mufradat, Arabic morphology, and Arabic syntax). From some of the material taught, namely about everyday mufradat and understanding of shorof in the isim file chapter. In this case, multiple intelligences are combined with neuroscientific theory between the interpersonal and intrapersonal intelligence centers in the right brain and left brain. This research has implications for the improvement and development of students in understanding Arabic material (quwaidul arabiyah) in today's Islamic boarding schools.